2016
DOI: 10.1177/2048872615589511
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease and worsening renal function in acute heart failure: different phenotypes with similar prognostic impact?

Abstract: Nearly a third of patients with acute heart failure experience concomitant renal dysfunction. This condition is often associated with increased costs of care, length of hospitalisation and high mortality. Although the clinical impact of chronic kidney disease (CKD) has been well established, the exact clinical significance of worsening renal function (WRF) during the acute and post-hospitalisation phases is not completely understood. Therefore, it is still unclear which of the common laboratory markers are abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 87 publications
0
21
0
Order By: Relevance
“…HF has several negative effects on kidney function but, at the same time, CKD can significantly impair cardiac function. This process is due to hemodynamic alterations, inflammatory and endothelial activation, parenchymal damage, increased neuroendocrine activity and other factors, which can influence in different ways the improvement or the worsening of both HF and CKD [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…HF has several negative effects on kidney function but, at the same time, CKD can significantly impair cardiac function. This process is due to hemodynamic alterations, inflammatory and endothelial activation, parenchymal damage, increased neuroendocrine activity and other factors, which can influence in different ways the improvement or the worsening of both HF and CKD [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…These patients are more susceptible for damage caused by hypertension because of the failure of intrarenal blood flow autoregulation due to activation of the tubulo-glomerular feedback which leads to opening the pre-glomerular capillaries and easier transmission of the systemic hypertension directly to the glomeruli. It was shown that increased intra-glomerular pressure is one of the leading factors in the pathogenesis of faster progression of CKD [35, 36]. …”
Section: Discussionmentioning
confidence: 99%
“…Although deterioration in renal function is one of the most important co‐morbidities and often complicates the natural course of hospital stay in patients with acute heart failure (AHF), the terminology and optimal assessment of renal function in this clinical condition remain controversial . In everyday practice, serum creatinine is used to monitor renal function, with a rise in its level traditionally considered as indicating worsening renal function (WRF) and linked with inevitably poor outcomes .…”
Section: Introductionmentioning
confidence: 99%